Food security under compound shocks: Can Lebanon produce its own Mediterranean food basket? - Daher, Bassel; Bachour, Roula; Yanni, Sandra F.; Koo-Oshima, Sasha; Mohtar, Rabi H. (Frontiers in Sustainable Food Systems, 2022)
As Lebanon faces compound challenges, a looming food security crisis is rapidly approaching, much of which could be attributed to the lack of long-term planning for sustainability in its agricultural sector. The disconnect between decision-makers within the agricultural sector, and other interconnected sectors is exacerbated by the lack of integrative national platforms and methodologies for quantifying the trade-offs associated with possible interventions. This study aims to: 1) identify and quantify the critical interconnections between water, energy, nutrition, and food systems in Lebanon; 2) develop a framework to quantify the trade-offs associated with adopting interventions within current water, energy, and agriculture portfolios and practices; 3) evaluate producers’ perceptions toward their willingness to implement proposed changes in crop production, renewable energy, and water reuse. Findings show that investing in locally producing Lebanon’s needs of broad beans, lentils, chickpeas, and peas, results in cost savings, increased nutritional value in the locally produced basket, and reduced reliance on foreign markets. In turn, this comes at additional water, energy, land and carbon footprints which needs to be accounted for. Given the uncertainty of future currency conversion rates, it becomes more critical to identify a strategic food basket that could be produced locally to reduce reliance on imports. Conclusions from this study can play a role in informing policymaking and planning in Lebanon, which could be adapted and replicated in other countries in the MENA Region.